1988
DOI: 10.1530/acta.0.1180521
|View full text |Cite
|
Sign up to set email alerts
|

7B2, a new protein secreted by human functionless pituitary tumours, in vitro

Abstract: Abstract. A novel pituitary protein, 7B2, of approximately 180 amino acids has been suggested to colocalise with LH in the pituitary gonadotropes. Increased secretion of LH is known to occur in functionless pituitary tumours. We have therefore measured 7B2 immunoreactive equivalents in the 24-h medium of explant pituitary cultures prepared from 17 functionless, 20 somatotropic, 16 PRL secreting and 8 corticotropic adenomas. A synthetic fragment corresponding to amino acids 23–39 of 7B2 was used to raise antise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The 7B2-null mice with Cushing’s disease may be saved early in life by an adrenalectomy (55). Neither our plasma ACTH tumours of Cushing’s patients (26,56), nor those studied by Natori et al (57,58) allow the conclusion that 7B2-IR levels in plasma are increased in Cushing’s patients, and corticotrophic adenomas have not shown increased 7B2 secretion in vitro , although 7B2 is concomitantly secreted with ACTH by AtT-20 tumourous cells in vitro (56). It has been suggested that the lethal phenotype that is exhibited by 7B2-null mice with a complex Cushing’s disease-like pathology, is due to intermediate lobe ACTH hypersecretion as a consequence of the interruption of PC2-mediated peptide processing, as well as undefined consequences of the loss of 7B2.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The 7B2-null mice with Cushing’s disease may be saved early in life by an adrenalectomy (55). Neither our plasma ACTH tumours of Cushing’s patients (26,56), nor those studied by Natori et al (57,58) allow the conclusion that 7B2-IR levels in plasma are increased in Cushing’s patients, and corticotrophic adenomas have not shown increased 7B2 secretion in vitro , although 7B2 is concomitantly secreted with ACTH by AtT-20 tumourous cells in vitro (56). It has been suggested that the lethal phenotype that is exhibited by 7B2-null mice with a complex Cushing’s disease-like pathology, is due to intermediate lobe ACTH hypersecretion as a consequence of the interruption of PC2-mediated peptide processing, as well as undefined consequences of the loss of 7B2.…”
Section: Discussionmentioning
confidence: 72%
“…7B2 cDNA cloning from various species has demonstrated the high evolutionary conservation of the 7B2 molecule, suggesting that 7B2 may be biologically relevant. In particular, the overall residue identity is extremely high (90–96%) among mammals, relatively high (67–83%) between mammals and frogs or fish, and low (17–22%) between vertebrates and invertebrates (26,27). Initially, 7B2 was revealed to be located in the pituitary gonadotrophs (26,27) and to respond to exogenous LH-releasing hormone (LHRH) (26).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…7B2 had not been found in normal or tumoral corticotroph cells (Deng et al, 1986;Suzuki et al, 1986;Venetikou et al, 1988;Steel et a[., 1988) until our recent results in the mouse tumour cell line AtT-20 (Vieau et al 1991b). These results had suggested that 7B2 had the potential to be a specific marker of non-pituitary ACTH secreting tumours in man.…”
mentioning
confidence: 93%